Trait continuity: Can parent-rated infant temperament predict HEXACO personality in early adulthood? - Kamarova, Sviatlana; Dunlop, Patrick; Parker, Sharon (WILEY, 2023)
Examining the Raine cohort study, we tested the trait continuity hypothesis by examining the extent that young adults' (25–29 years old) self-reported HEXACO personality can be statistically predicted from multi-dimensional parental temperament ratings collected in infancy (1–2 years old). The study incorporated a lagged design (two waves), a large sample size (n = 563), and examined both temperament and personality as both dimensions and profiles. Overall, we found very limited evidence of trait continuity, with generally very weak and few statistically significant observed associations of infant temperament with early adulthood personality. Relations were weak whether profile or dimension-based operationalizations of both phenomena were adopted. Additionally, controlling for sex affected the relations of temperament and personality only to a small extent for most of the traits, and moderation effects of sex were generally zero-to-trivial in size. Altogether, parent-rated temperament in infancy seems to provide little information about HEXACO personality in early adulthood.